The Inferior Alveolar Nerve of the Horse: Course and Anatomical Relationship with Mandibular Cheek Teeth. (3rd September 2014) - Iacopetti, I.; Faughnan, M.; Bono, S.; Cozzi, B.; Facchini, C.
Summary The precise location of neurovascular structures within the relatively long mandibular canal of the horse is of paramount importance in surgical procedures of the area. The inferior alveolar nerve (IAN) enters the mandibular canal on the medial (lingual) surface of the mandible and innervates all the mandibular teeth. During its course, the nerve moves laterally, crossing the roots of the inferior cheek teeth. However, the exact anatomical relationships occurring between the IAN and the roots of the equine mandibular cheek teeth have not been described in detail. In this study, the mandibles of 40 horses were examined with CT scans and then used for bilateral detailed anatomical dissection, to assess the path of the IAN and its relationship to the roots of the lower cheek teeth. The data obtained show that the equine IAN is located ventral to the apices of the molar teeth (311/411, 310/410, 309/409 according to the Triadan numerical system). At the level of PM4 (308/408), the IAN is located on the lingual side of the roots and coronally to its apices. At the level of PM3 (307/407), the IAN is then found on the lingual side of the roots but in proximity to the apices. In 2 of 40 horses (=5%), the IAN moves towards the lingual side between the mesial and the distal root of PM4. Our observations are valuable for planning a surgical approach to the ventral side of the mandible in the horse and to avoid potential post‐operative complications.